Mental healthcare in Brazilian spiritism: the aesthetics of healing - Kurz, Helmar (Explorations in mental health, 2024)
Introduction: Diversification of Mental Health -- Spiritism and Mental Health -- Healing Cooperation: Therapeutic Spaces of Brazilian Spiritism -- Aesthetics of Healing: A Sense of Self and Other -- Translocal Networks and Politics of Care -- Conclusion: Voices of Good Sense.